FRI0072 PREDICTING SARCOPENIA AND OBESITY BY MEASURING THIGH MUSCLE AND FAT THICKNESS BY ULTRASOUND IN PATIENTS WITH RHEUMATOID ARTHRITIS: FROM THE CHIKARA STUDY. (June 2019) - Yamada, Yutaro; Tada, Masahiro; Mandai, Koji; Hidaka, Noriaki; Inui, Kentaro; Nakamura, Hiroaki
Abstract : Background: Rheumatoid arthritis (RA) patients often have sarcopenia. The thickness of the quadriceps muscle, easily measurable by ultrasound (US), is known to be related to skeletal muscle mass, and its decreased thickness may suggest sarcopenia. Objectives: To investigate the utility of US for predicting sarcopenia by examining the anterior thigh in RA patients. Methods: Ninety-four patients (66 female) enrolled in the prospective CHIKARA study (UMIN000023744) underwent US muscle (MT) and fat thickness (FT) examinations of the anterior thigh. Muscle and body fat mass were also examined by a body composition analyzer (MC-780A; TANITA, Tokyo, Japan). Whether MT and FT can predict sarcopenia and obesity was also examined. Sarcopenia was diagnosed based on the Asian Working Group on Sarcopenia definition, and obesity was diagnosed by% body fat (%BF). Results: MT was significantly lower in RA patients with sarcopenia than in those without (24.8 ± 3.5 mm vs. 29.6 ± 3.8 mm, p=0.01). MT was related to sarcopenia (males r=0.56, p=0.02; females r=0.32, p=0.01). The MT cut-off value for sarcopenia was 24.7 mm in males and 19.7 mm in females on receiver operating curve (ROC) analysis. FT was correlated with%BF (males r=0.66, p<0.01; females r=0.62, p<0.001).%BF was estimated by 2.21FT+7.28 in males and 1.45FT+14.46 in females by a simple linear regression model. This means that FT>8.0 mm in males and FT>10.7 mm in females indicate obesity (Table 1 ). When assessing the accuracy of these cut-off values, the kappa values were 0.541 and 0.469, respectively Conclusion: Sarcopenia and obesity can be predicted by US examination of the anterior thigh in RA patients. Reference: [1] Kawai H., Kera T., Obuchi S., et al. Morphological and qualitative characteristics of the quadriceps muscle of community-dwelling older adults based on ultrasound imaging: classification using latent class analysis. Aging Clin Exp Res. 2018; 30:283–29. Acknowledgement: Yutaro Yamada Disclosure of Interests: Yutaro Yamada Speakers bureau: Abbvie, Chugai, Mitsubishi Tanabe, Masahiro Tada Speakers bureau: Abbvie, Astellas Pharma, Bristol-Myers Squibb, Chugai Pharmaceutical, Eisai, Janssen Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Ono Pharmaceutical, Pfizer Japan, Takeda Pharmaceutical, Koji Mandai: None declared, Noriaki Hidaka: None declared, Kentaro Inui Speakers bureau: Takeda Pharmaceutical, Pfizer Japan, Daiichi-Sankyo Co.Ltd., Abbvie, Mitsubishi Tanabe Pharma Corporation, Janssen Pharmaceutical, Chugai Pharmaceutical, Ono Pharmaceutical, Eisai Co.Ltd., Eli-Lilly, Nippon Kayaku Co., Ltd., Maruho Co., Ltd, Kaken Pharmaceutical Co., Ltd., Hiroaki Nakamura: None declared